Cover cropping to prepare degraded lands for forestry: challenges and opportunities - Stavi, Ilan; Bebre, Ieva; Dimitrova, Anastazija; Stanturf, John (Springer Science and Business Media LLC, 2023)
Cover cropping is practiced in conservation agriculture to preserve soil and water resources, alleviate soil compaction, sequester organic carbon, and control weeds. Meanwhile, cover cropping is rarely used in forestry, probably due to the lack of awareness of this management practice. In this short essay, we discuss the concept of utilizing cover crops to prepare degraded lands for afforestation or reforestation projects. The benefits of this practice are similar to those in agriculture. The risks of this practice are mostly related to plant-plant interactions, and particularly, to the potential competition for resources with the target trees. As such, this practice should be implemented cautiously, to prevent adverse impacts on the forest system. Also, attention should be paid to ensure the delivery of ecosystem services and functions by the target land. Further, the co-use of complementary practices may be considered to accelerate the success rate of cover cropping in degraded lands designated for afforestation and reforestation. Among these practices, application of soil additives, such as composts, manures, and biochars, may be useful in increasing soil concentrations of organic carbon and nutrients, thus improving soil quality and fertility. Additional complementary active practices may be the direct seeding or planting of nurse shrubs and trees, as well as the inoculation of soil surface with biocrust slurries, aimed to increase ecosystem complexity by forming a multi-story vegetation structure. Recommendations and guidelines for implementing cover crops in forestry should be site-specific and case-dependent, and consider both the desired benefits and potential risks.
Keywords: Allelopathy · Climatic change · Facilitation · Leguminous species · Mixed cover crops · Nature-based solutions